A-, B- and C-type starch granules coexist in root tuber of sweet potato. (January 2020) - Guo, Ke; Zhang, Long; Bian, Xiaofeng; Cao, Qinghe; Wei, Cunxu
Abstract: C-type starches isolated from different colored root tubers of sweet potatoes were investigated to reveal the distribution of A- and B-type crystals using differential scanning calorimetry (DSC), X-ray diffractometry (XRD), and hot stage microscopy. The results showed that starches from different colored sweet potatoes all exhibited CA -type XRD patterns and wide DSC thermal peak curves. The thermal peaks could be highly fitted into three peaks, defined as Peak 1, 2 and 3, according to their gelatinization temperatures (GTs) from low to high. When starch was gelatinized in KCl solution, the peak temperature of Peak 1 increased slightly and then decreased, but those of Peak 2 and 3 increased first rapidly and then slowly with increasing KCl concentration. Starch was gelatinized from the interior to exterior of granules, and could be divided into three groups, defined as Group 1, 2 and 3, according to their GTs from low to high, corresponding to Peak 1, 2 and 3 of DSC thermogram, respectively. The starch granules in Group 2 had significantly wider GT range than those in Group 1 and Group 3. The starch granules with increasing GT exhibited XRD patterns from CA - to A-type and DSC thermograms from wide three-peak to narrow single peak. B-type starch granules had higher short-range ordered structure than A-type starch granules. The above results indicated that B-, C-, and A-type starch granules with GT from low to high coexisted in root tubers of sweet potato. Graphical abstract: Image 1 Highlights: C-type starches from different colored sweet potatoes had wide thermal peak curves. 3 peaks with different gelatinization temperatures (GTs) were fitted from peak curve. 3 groups of starch granules with different GTs were also detected during heating. Starches with low and high GTs were B- and A-type starch granules, respectively. Starch with middle GT had both A- and B-type crystals coexisted in the same granule.